Communicating About Sound with Words : A Comparative Study Investigating the Relation Between Selected Adjectives and Spectral Qualities Evaluated by Musicians and Audio Engineers - Martin, Emilia (2016)
When communicating spectral qualities in audio and music productions musicians and audio engineers constantly use different words such as adjectives for describing a perception of a desired sound. Attempting to improve communication between collaborators in audio and music productions this research project investigated if musicians and audio engineers associate the adjectives thick (grötigt), nasal (nasalt), sharp (skarpt) and airy (luftigt) with same frequency ranges. A listening experiment with 20 music students from Luleå University of Technology was conducted were the task was to match differently filtered audio samples with a given adjective that the subjects associated the sample most to. The experiment was a replica from a prior study where audio engineers associations got examined. The musicians’ data were treated with a chi square goodness of fit test and the comparison between musicians and audio engineers data were treated with a Fisher’s exact test. Results show that a majority of the participating musicians and audio engineers associate the adjectives thick and nasal with the same frequency ranges. Validerat; 20160519 (global_studentproject_submitter)